Strategi Pemasaran Go Digital Mitra UMKM Rumah BUMN Bandar Lampung (Studi Kasus Coffee Anjosia) - Purnomo, Agus (Business Perspective Journal, 2023)
In the digital era, the role of technology is very important in helping MSMEs to market their products and services. The existing problems include sales results fluctuating and tending to decline, the company not being right in marketing. This research aims to evaluate the marketing strategy of Rumah BUMN Bandar Lampung MSMEs through the application of Go Digital to MSME Partners, with a case study of the Coffee Anjosia business. The method used is descriptive qualitative by obtaining data through interviews, observation and document analysis. The results of the analysis show that the implementation of Go Digital at Rumah BUMN Bandar Lampung MSME Partners has an important role in helping MSMEs market their products and services. An effective strategy can be achieved by maintaining and increasing high consumer demand, creating training plans for Anjosia employees related to adapting to current technology in managing business marketing, providing special prices to loyal customers for large purchases, and utilizing social media such as Instagram by routinely create content every week on social media. Keywords: marketing strategy; go digital, MSMEs, Anjosia Coffee